2021
DOI: 10.1111/jrh.12570
|View full text |Cite
|
Sign up to set email alerts
|

An examination of telehealth policy impacts on initial rural opioid use disorder treatment patterns during the COVID‐19 pandemic

Abstract: Purpose Tracking changes in care utilization of medication for opioid use disorder (MOUD) services before, during, and after COVID‐19‐associated changes in policy and service delivery in a mixed rural and micropolitan setting. Methods Using a retrospective, open‐cohort design, we examined visit data of MOUD patients at a family medicine clinic across three identified periods: pre‐COVID, COVID transition, and COVID. Outcome measures include the number and type of visits (in‐person or telehealth), the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 13 publications
3
36
0
Order By: Relevance
“…This change rebound in prescription supports that despite the COVID-19 pandemic and social distancing requirements, with policy adjustments and clinical practice evolution, prescribers in WV were only temporarily inhibited in the distribution of MOUD. This rebound in prescribing, after telemedicine and social distancing measures are put in place, can be expected as previous studies on telemedicine delivery of MOUD show improved retention of patients with OUD ( Hughes et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This change rebound in prescription supports that despite the COVID-19 pandemic and social distancing requirements, with policy adjustments and clinical practice evolution, prescribers in WV were only temporarily inhibited in the distribution of MOUD. This rebound in prescribing, after telemedicine and social distancing measures are put in place, can be expected as previous studies on telemedicine delivery of MOUD show improved retention of patients with OUD ( Hughes et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 69%
“…Telemedicine is effective for opioid agonist therapy delivery ( Morin, Parrotta, Eibl, & Marsh, 2021 ), including the induction of therapy ( Tofighi et al, 2019 ). Hughes and colleagues, report that primary care-based MOUD visits increased with telehealth ( Hughes et al, 2021 ). A phone-based MOUD telehealth program was similarly effective in San Francisco ( Mehtani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on how programs may leverage these strengths to expand scopes of service in the pandemic era should be prioritized. For example, the success of telemedicine in providing opioid use disorder treatment in rural areas [ 32 ], in concert with evolving policies related to reimbursement, provides an opportunity to explore how novel mobile and other low-threshold care may be linked to or delivered through harm reduction programs. Given high rates of governmental distrust in people who use drugs, particularly those in rural communities, harm reduction service providers as trusted messengers could be empowered to provide public health messaging around COVID-19 information and vaccination [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to the growing body of research examining the impact of SAMHSA exemptions implemented during the COVID-19 pandemic. Research has reported positive outcomes from post-COVID telemedicine buprenorphine-based treatment programs made possible through loosened restrictions (Hughes et al, 2021;Tofighi et al, 2021). Regulatory bodies were concerned with increase diversion as a result of increases in take home methadone doses.…”
Section: Discussionmentioning
confidence: 99%